Mobile Big Data A Roadmap from Models to Technologies - Skourletopoulos, Georgios; Mastorakis, George; Mavromoustakis, Constandinos X.; Dobre, Ciprian; Pallis, Evangelos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on the latest advances in mobile technologies for collecting, storing and processing mobile big data in connection with wireless communications. It presents novel approaches and applications in which mobile big data is being applied from an engineering standpoint and addresses future theoretical and practical challenges related to the big data field from a mobility perspective. Further, it provides an overview of new methodologies designed to take mobile big data to the Cloud, enable the processing of real-time streaming events on-the-move and enhance the integration of resource availability through the 'Anywhere, Anything, Anytime' paradigm. By providing both academia and industry researchers and professionals with a timely snapshot of emerging mobile big data-centric systems and highlighting related pitfalls, as well as potential solutions, the book fills an important gap in the literature and fosters the further development in the area of mobile technologies for exploiting mobile big data.
Part I - Introduction To Mobile Big Data Paradigm -- Big Data Analytics: Applications, Prospects And Challenges -- Levering Mobile Cloud Computing For Mobile Big Data Analytics -- Game Theoretic Approaches In Mobile Cloud Computing Systems For Big Data Applications: A Systematic Literature Review -- Part II - Architectures, Applications And Services For Mobile Big Data.-Evidence-Aware Mobile Cloud Architectures -- Context-Awareness In Location Based Services In The Big Data Era -- Mobile Big Data In Vehicular Networks: The Road To Internet Of Vehicles -- Part III - Data Management For Mobile Big Data.-Mobile Distributed Complex Event Processing - Ubi Sumus? Quo Vadimus?.-Electromagnetic Interference And Discontinuity Effects Of Interconnections On Big Data Performance Of Integrated Circuits -- Evaluating Decision Analytics From Mobile Big Data Using Rough Set Based Ant Colony -- Energy-Aware Issues For Handling Big Data In Mobile Cloud Computing -- Part IV - Industrial Practices Of Mobile BigData-Driven Models -- Big Data - A New Technology Trend And Factors Affecting The Implementation Of Big Data In Australian Industries -- Extending The SANA Mobile Healthcare Platform With Features Providing ECG Analysis.-Social Networking In Higher Education In India.
Keywords: Computational intelligence; Data mining; Artificial intelligence; Computational Intelligence; Data Mining and Knowledge Discovery; Artificial Intelligence